2016
DOI: 10.1002/14651858.cd011537.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine administration of human chorionic gonadotropin (hCG) for subfertile women undergoing assisted reproduction

Abstract: The pregnancy outcome for cleavage-stage ETs using an IC-hCG dose of 500 IU or greater is promising. However, given the small size and the variable quality of the trials and the fact that the positive finding was from a subgroup analysis, the current evidence for IC-hCG treatment does not support its use in assisted reproduction cycles. A definitive large clinical trial with live birth as the primary outcome is recommended. There was no evidence that miscarriage was influenced by intrauterine hCG administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The dosages and types of hCG varied among the six RCTs. A meta-analysis published in 2016 found that a hCG dose of 500 IU or greater showed promise as the dosage before cleavage-stage ETs, but a hCG dose less than 500 IU before cleavage-stage ETs had no effect, and a dose of 500 IU or greater before blastocyst-stage ETs also showed no benefit [ 30 ]. Mansour’s study [ 3 ] reported that a 100- or 200 IU-hCG injection did not increase the pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…The dosages and types of hCG varied among the six RCTs. A meta-analysis published in 2016 found that a hCG dose of 500 IU or greater showed promise as the dosage before cleavage-stage ETs, but a hCG dose less than 500 IU before cleavage-stage ETs had no effect, and a dose of 500 IU or greater before blastocyst-stage ETs also showed no benefit [ 30 ]. Mansour’s study [ 3 ] reported that a 100- or 200 IU-hCG injection did not increase the pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…The inconclusiveness is attributed to the heterogeneity of the trials (dosage, timing, origin of hCG source (urinary vs. recombinant) and developmental stage of embryos transferred). A sub-group investigation of the current Cochrane database analysis supports a benefit of a minimum of 500 IU hCG infused before cleavage stage embryos are transferred [13]. However, all babies born in our clinical setting resulted from blastocyst transfers and infusion of 500 IU hCG 10–15 min before transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Another procedure focuses on influencing the endometrial receptivity. In this regard, methods like the endometrial injury in the cycle before the controlled ovarian stimulation to provoke an influx of immune competent cells [12] or the use of human chorionic gonadotropin (hCG) infusion prior to an embryo transfer are incorporated in therapy protocols but are discussed in contradictory terms in the literature [13,14]. HCG is produced by the syncytiotrophoblast and maintains the blood supply for the developing placenta.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such sources of possible bias have been addressed by a recent Cochrane review [45]. The authors considered an overall meta-analysis on live birth and clinical pregnancy rates to be rather impossible due to high heterogeneity.…”
Section: Hcg and Clinical Applications In Assisted Reproduction Tementioning
confidence: 99%